Pseudo-nitzschia kodamae sp. nov. (Bacillariophyceae), a toxigenic species from the Strait of Malacca, Malaysia - Sing, Tung Teng; Hong, Chang Lim; Po, T.L; Viet, Ha Dao; Bates, Stephen S.; Chui, P.L (Elsevier Ltd., 2014)
A recent field survey of Pseudo-nitzschia species from coastal waters of Malaysia demonstrated the presence of a novel morphotype, P. sp. Port Dickson, in the Strait of Malacca. In this study, we revisited the site and established five clonal cultures of this morphotype, assessed the strains’ morphology and genetics, and delineated it as a novel species. As observed by electron microscopy, these strains showed morphological features identical to those of the previous field specimens designated as P. sp. Port Dickson. The cells differ from other Pseudo-nitzschia species in the P. pseudodelicatissima complex sensu lato by their lower densities of fibulae, striae and band striae in 10 mm. Molecular data of the nuclear encoded large subunit ribosomal rRNA gene and the internal transcript spacer region (ITS) further supported the delineation of this novel lineage. Based on both morphological and molecular data, P. sp. Port Dickson is considered to represent a new species, for which we propose the name Pseudo-nitzschia kodamae sp. nov. Production of domoic acid (DA) in the strains was examined by FMOC–LC–FLD. Only strains of P. kodamae were observed with a peak corresponding to DA, giving a concentration of 1.2– 42.5 pg DA cell1. Screening of Pseudo-nitzschia caciantha, Pseudo-nitzschia batesiana, Pseudo-nitzschia fukuyoi and Pseudo-nitzschia lundholmiae cultures from the same waters, however, showed no detectable DA. This is the first report of a potentially toxigenic Pseudo-nitzschia species from the region.